2006
DOI: 10.3201/eid1210.060424
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Poultry-to-Human H5N1 Transmission, Southern Cambodia, 2005

Abstract: Transmission is low despite extensive human contact with poultry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
64
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 12 publications
12
64
0
1
Order By: Relevance
“…Furthermore, the clade 1 infl uenza virus (H5N1) strains that infected poultry and humans in Thailand during 2004 were antigenically and genetically distinct from the clade 0 infl uenza virus (H5N1) strains that caused the 1997 outbreak in Hong Kong (11). Our fi nding of no serologic evidence of asymptomatic or mild infl uenza (H5N1) infection among Thai villagers is consistent with fi ndings from smaller infl uenza virus (H5N1) seroprevalence studies among workers in live poultry markets in the People's Republic of China (12), among villagers exposed to backyard poultry infected with clade 1 infl uenza virus (H5N1) in rural Cambodia (13), among poultry workers exposed to poultry infected with clade 2.2 infl uenza virus (H5N1) in northern Nigeria (14), and among poultry farmers exposed to poultry infected with clade 1 infl uenza virus (H5N1) in Thailand (7). Results of studies conducted since 2004 thus suggest that the risk for infl uenza (H5N1) infection is low among persons exposed to infected poultry; however, our fi nding of no serologic evidence of asymptomatic or mild infl uenza (H5N1) infection among Thai villagers suggests that the high case-fatality proportion in Thailand (17 deaths among 25 persons with confi rmed infection) may accurately refl ect the severity of the infection in Thailand.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the clade 1 infl uenza virus (H5N1) strains that infected poultry and humans in Thailand during 2004 were antigenically and genetically distinct from the clade 0 infl uenza virus (H5N1) strains that caused the 1997 outbreak in Hong Kong (11). Our fi nding of no serologic evidence of asymptomatic or mild infl uenza (H5N1) infection among Thai villagers is consistent with fi ndings from smaller infl uenza virus (H5N1) seroprevalence studies among workers in live poultry markets in the People's Republic of China (12), among villagers exposed to backyard poultry infected with clade 1 infl uenza virus (H5N1) in rural Cambodia (13), among poultry workers exposed to poultry infected with clade 2.2 infl uenza virus (H5N1) in northern Nigeria (14), and among poultry farmers exposed to poultry infected with clade 1 infl uenza virus (H5N1) in Thailand (7). Results of studies conducted since 2004 thus suggest that the risk for infl uenza (H5N1) infection is low among persons exposed to infected poultry; however, our fi nding of no serologic evidence of asymptomatic or mild infl uenza (H5N1) infection among Thai villagers suggests that the high case-fatality proportion in Thailand (17 deaths among 25 persons with confi rmed infection) may accurately refl ect the severity of the infection in Thailand.…”
Section: Discussionsupporting
confidence: 67%
“…Although the media reported that a corporate-run poultry farm, Biman Poultry Complex, was the fi rst avian infl uenza-affected farm in Bangladesh, our investigation found it to be the third. Of the 5 breeder farms, 2 had imported chicks from the United States and 1 from (6,7), genetic variation in receptors (8)(9)(10), poor surveillance of disease in humans, or using antiviral drugs during culling of birds.…”
Section: The Studymentioning
confidence: 99%
“…La contamination humaine se fait au contact d'oiseaux (principalement des volailles) infectés par le virus H5N1, malades ou morts [9], mais la transmissibilité à l'homme est faible [10]. Le premier cas humain, hormis celui de 1997, a été rapporté en 2003.…”
Section: Cas Humainsunclassified